Detection of ionic conductivity and moisture content of various liquids using microwave technique - Abd Rahman, Mohd Amiruddin (2011)
Measurement of ionic conductivity and moisture content of liquid is important because such information give indication about quality and also composition of elements of liquid. Previously microwave sensors are mainly used to determine moisture content in liquid. However, the microwave sensor may also be used to measure the conductivity at lower microwave frequency range. At present, detection of conductivity is done at low frequency and no previous efforts using microwave technique is considered because of the cost. However, a microwave system which could do simultaneous detection could overcome that problem. A quasi-transverse electromagnetic technique employing variational method is used to simulate the behaviour of attenuated wave of the sensing element of the microwave microstrip sensor. Three different operating frequencies at 300 MHz, 2 GHz and 5 GHz is chosen particularly for detection of the attenuation of the sensor where the first two is for conductivity detection and the last is for moisture content detection. The calculated results demonstrate that the attenuation is a function of permittivity of liquid. Also, permittivity is related to the conductivity and moisture content of liquid at low and high frequency respectively. A computer program using Fortran programming language is used for the calculation. The U-shaped microwave microstrip system is based on the transmission coefficient of the microstrip sensors. The system utilises two oscillators that act as the microwave source which operates at above mentioned frequencies. Two crystal detectors are placed in the system to measure input and output voltage so that total attenuation of the system can be determined. Conductivity and moisture content standard measurement are done using a commercial conductivity meter and oven drying method respectively. Comparison of the insertion loss of the microstrip sensor system from calculation with attenuation of microstrip sensor alone shows excellent correlation of 0.9945. Established empirical relationship between insertion loss and conductivity at 300 MHz and 2 GHz gives correlation coefficient of 0.6334 and 0.9431 respectively. Another empirical relationship of insertion loss and moisture content at 5 GHz shows good fit at 0.9688. Evaluation of the measured conductivity and moisture content using developed system with standard measurement gives correlation coefficient of 0.3282 (300 MHz), 0.9435 (2 GHz). and 0.9781 (5 GHz). The main limitation of the developed system is in terms of measurement of conductivity of fresh latex samples at 300MHz since the variation of conductivity is less than 0.2 S/m. The moisture content measurement shows very good sensitivity at 1% change of moisture content. The results present that the developed microwave system is possible to be used for simultaneous measurement of conductivity and moisture content of liquids. Further enhancement may be made to improve the resolution of conductivity measurement at low frequency. The system could be made portable which reliable for in-situ field measurement.